ARTERIAL HYPERTENSION IN MINE PIT MINERS - Kulic, Ljiljana; Krstovic Spremo, Vesna; Jovanovic, Jovica; Galjak, Milivoje; Bojceski, Oliver; Jovanovic, Jovana (HEALTH CARE, 2023)
Introduction/Aim: Arterial hypertension is common both in the general population and in production workers, especially those who work in jobs with special working conditions. The aim of this work is to analyze the frequency of occurrence and characteristics of arterial hypertension in pit miners in relation to physical workers. Methods: The cross-sectional study included 321 miners of the "Lece" Mine (Serbia) and 150 manual workers who had never worked in the pit (control group). The obtained results were analyzed in relation to the type and severity of arterial hypertension and the age of subjects. In order to diagnose hypertension, a clinical examination was performed. The chi-square test was used in the statistical analysis of data. Results: Arterial hypertension was significantly (p˂0.001) more often present in miners (35.2%) than manual workers (14.5%). At least 95% of the subjects of both investigated groups had primary hypertension. The frequency of hypertension increased with age in both studied groups and was highest in the age group of 46-55 years. There was no significant difference between the treated groups in relation to the frequency of hypertension by age group, although miners in the oldest age group had moderate (31.5%) and severe hypertension (13.0) more often than manual workers (28.6% and 7. 1%). Conclusion: The more frequent occurrence of hypertension, as well as the predominance of moderate and severe hypertension, in miners compared to physical workers, points to the possibility that working conditions influence the onset of this disease.
Keywords: arterial hypertension, age, miners, pit, manual workers